(untitled) (Manarul Qur’an: Jurnal Ilmiah Studi Islam, 2016)
This research was aimed; 1) to know the meaning of kyai as a learning leader at the Pesantren Ulumul Qur’an, 2) to know a leadership style in learning at the pesantren of ulumul qur’an, 3) to know the handicap of kyai in doing a learning leadership. This research used a qualitative method. The subject of reserach were such as kyai, teachers and students. Technique of data collecting used particpant observation, interview, and study of document. And the analysis of data used interactive analysis of miles and huberman that ie; data collection, data reduction, data display and conclusion Result of research have showed that the meaning kyai of learning leader were a manager of learning, a designer of learning, a decision maker, and an evaluator of learning. The leadership style of kyai in learning such as uswatun hasanah style and istiqomah style. Trick of kyai in learning leeadership were regeneration, lapanan activity, habituation and roan or teamwork. Finally, the handicap of santri in learning cativity such as feeling of lazy, less seriously, and no discipline, and the handicap of kyai in learning leadership were busy in campus, village surounding and social activity.